Pertumbuhan Madiun Sebagai Kota Gadis 2018-2023 - Imma Latifa; Pambudi Handoyo (FKIP, Universitas Palangka Raya, 2023)
The city of Madiun is nicknamed the City of Girls which is an acronym for trade, education and industry. These nicknames are certainly pinned not without reason. Because nicknames are generally taken from characteristics or elements that are highlighted in something. This study aims to find out how the city of Madiun has grown according to its nickname as the City of Gadis. The method used is literature study. Based on the secondary data that has been collected above, it can be concluded that the city of Madiun as a city of Gadis does not fully deserve this title. Because several problems that show the negligence of the Madiun city government in the education sector and industrial factories still need special attention. On the other hand, in the trade sector, the city of Madiun continues to grow in a positive direction. This needs to be accompanied by efforts to continue to maintain and improve the trade sector in the city of Madiun